Queiroziella gen. nov., a new genus of jumping plant-lice (Hemiptera, Psyllidae) from Southern Brazil associated with Mimosa scabrella (Leguminosae) - Burckhardt, Daniel (Zootaxa, 2021)
Queiroziella gen. nov., a new genus of Psylloidea (Psyllidae, Ciriacreminae), is erected for five new species developing on the multipurpose tree Mimosa scabrella (Leguminosae, Caesalpinioideae, mimosoid clade): viz. Queiroziella erato sp. nov., Q. euterpe sp. nov., Q. melpomone sp. nov., Q. terpsichore sp. nov. and Q. thalia sp. nov. Another species from Paraguay, associated with an unidentified Mimosa species, is transferred to the new genus as Queiroziella borealis (Burckhardt, 1987), comb. nov., from Zonopelma (Aphalaroidinae). The new taxa are diagnosed, described and illustrated, and keys are provided for the identification of adults and immatures. Morphologically, Queiroziella resembles Heteropsylla which is also associated with mimosoid legumes and with which it may be closely related. As their host, the new species are restricted to Southern Brazil. Queiroziella euterpe, Q. melpomone and Q. terpsichore are reported from the states of Paraná, Rio Grande do Sul, Santa Catarina and São Paulo, Q. thalia from Paraná and São Paulo, and Q. erato from Paraná. No clear phenological patterns were found though it seems that high psyllid populations coincide with new flush of the host plants. Despite that the psyllids occur sometimes in very high numbers, no visible damage could be detected on host trees. On the other hand, the honeydew of the psyllids may provide a food source for honey-bees during non-flowering periods of Mimosa scabrella.